A nyugat-mongóliai dzahcsinok és népdalaik rövid ismertetése - Fahidi, Csaba (Távol-keleti Tanulmányok, 2018)
The purpose of this study is to introduce some of the folk songs of the Zakchin Mongolian people, a minor ethnic group living in Western Mongolia. In parallel with the original texts, the songs are translated into Hungarian in order to make them accessible to the Hungarian readers. Brief explanations related to certain songs are also offered. The basis of this study is a field research among the Zakchins in 2015 when the author collected several songs. Furthermore, I also clarify the historical background and briefly introduce the nature and types of Mongolian folk songs.